PENYERAPAN TENAGA KERJA PADA PROYEK PENAWARAN MODAL DALAM NEGERI DI PROPINSI MALUKU - Ummi Duwita (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2013)
This study aims to find out the amount of absorption of labor on the project in the province of Maluku domestic investment PMDN. However, the absorption of labour not only become the main focus of this analysis. The analysis method used is a quantitative method. Where quantitative aspect such us. the number of projects were analyzed, and production capacity of absorption of labor. Results of the analysis show that capital investment projects in the country directly to the addition of the influential budget development, capital investment projects In the country (PMDN) is also very influential in open employment opportunities as well as absorption of manpower there during the years 2005-2010 although absorption showed fluctuations. Therefore, it needs to be improved promotion-promotion of potential areas by Maluku Province for easy BKPMD is known by both national and Foreign investors so that there is a motivation from them to infuse capital in MalukuDOI: 10.15408/sjie.v2i2.2424